Curcumin Inhibits Mitochondrial Injury and Apoptosis from the Early Stage in EAE Mice. (27th April 2014) - Feng, Jinzhou; Tao, Tao; Yan, Weiping; Chen, Cindy Si; Qin, Xinyue
Abstract : The exact pathophysiological change concerning mitochondrial injury and oligodendrocyte apoptosis in MS and EAE model is still unknown. Whether curcumin is able to inhibit mitochondrial injury and suppress the apoptosis in the early stages of MS/EAE is still unclear. We first explored mitochondrial injury and apoptosis at different time points p.i. in C57 BL/6 EAE mice. We then explored the effects of curcumin on mitochondria and apoptosis. Results showed that mitochondrial injury can be observed 3 days p.i. Apoptosis in the spinal cord occurred 3 days p.i. and the apoptotic cells were shown to be oligodendrocytes and neuronal cells. Curcumin significantly reduced the number of apoptotic cells and inhibited the upregulation of cyt-c, caspase-9, and caspase-3 at 7 days p.i. in the EAE mice. These observations demonstrate that mitochondrial injury and oligodendrocyte/neuronal apoptosis occur in the early stages of EAE. Curcumin can inhibit apoptosis in EAE mice which maybe act through protection of mitochondrial injury and inhibition of the intrinsic apoptotic pathway.